(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2025)
The research aims to measure the role of social responsibility reports in enhancing disclosure and transparency among Iraqi private banks by providing additional disclosure in the financial statements. To achieve the goal of the research, the private Iraqi banks included in the Iraq Stock Exchange were chosen as a society for research, and four private banks (commercial and Islamic) were chosen as a sample to implement the research in order to carry out the selected sample issuing sustainable reports. A list of examination was used to indicate the extent of social responsibility reports contributed to enhancing the disclosure of banks based on sustainability reports issued by the bank and through the use of descriptive and inferential statistics measures, social responsibility data for the banks sample was analyzed. The researchers have reached several conclusions, the most important of which is the weak level of disclosure in social responsibility reports by banks and the lack of impact of current social responsibility reports on enhancing accounting disclosure in Iraqi banks listed on the Iraq Stock Exchange. The research presented a set of recommendations, the most important of which is the need for Iraqi banks to rely on comprehensive and regular reports on their activities in social responsibility to ensure the promotion of transparency and sustainability of their financial performance.